Field performance evaluation on dye-sensitized solar cell mini greenhouse in the tropics - Roslan, Nadirah (2021)
In many countries modern solar greenhouses that were developed by incorporating solar Photovoltaic (PV) (crystalline silicon based) into the agricultural greenhouses are currently being implemented. With this development, farmers will be able to generate income from both agricultural activity output and electrical generation. However, the most challenges manifested by PV greenhouses are to strike a balance between PV roofs and plants since conventional PV (Si based) is opaque to sunlight. The distribution of sunshades by PV panels above the greenhouse follows a linear correlation with the cover ratio. Therefore, semi-transparent DSSC; third generation of solar PV cells is the perfect choice in greenhouse application due to its unique characteristics such as various colour and transparency, versatility in scaling and low fabrication cost. In addition, DSSC's specific colour (determined by the dye) can serve as a plant growth regulator or photoselective shading that adsorbs and manipulates the greenhouse spectral irradiation. The Dynamic Dye-sensitized solar cell Mini Greenhouse (DDMG) has been developed and fabricated to maximize the use of light (PAR wavelength) that is important to the plant photosynthesis process, while the other wavelengths are used to generate electricity. The field test was carried out to determine DDMG's performance by means of examining Misai Kucing's sustainability within this prototype. To assess the effects and contributing factors, microclimate parameters such as temperature, relative humidity (RH), Vapour Pressure Deficit (VPD) and Photosynthetic Photon Flux Density (PPFD) were measured. To determine the feasibility of the DDMG, the experimental data were compared with the glass greenhouse as control. From the experiment and findings, it is observed that the performance of DDMG is related to internal microclimate greenhouse which is consequently affect the sustainability and growth of Misai Kucing cultivated in this prototype. From this analysis, semitransparent shading of the DSSC reduces air temperature by 1.47°C and raises relative humidity by 10.91%. Moreover, the average VPD (1.07 kPa) for DSSC greenhouse is an ideal for greenhouse. Unlike un-shaded greenhouse (control), the VPD is 1.63 kPa while maximum PPFD ranging from 1363.6 to 1798.4 μmolm-2s-1 which can cause plant stress. From an agronomic perspective, Misai Kucing cultivated under red DSSC shading tends to be slightly higher in branch number, size of leaves and total dry weight but slightly lower in plant height and stem diameter when compared with control greenhouse. Aside from the above, manipulation of spectral irradiation under red DSSC shading has been successfully achieved and demonstrated using a spectrometer. The results showed that spectral irradiance such as UV, blue and green were filtered out except red light (600-826nm) was transmitted through DSSC photo-selective shading. The DSSC modules generate a DC voltage, electric power, Fill Factor (FF) and efficiency with a maximum recording DC current of 0.119A, 2.081W, 1.148, and 2.907% respectively. This study enhances farming technology and creates knowledge gaps (by providing field measurement) and perspectives for policy makers and stakeholders in agro-PV industry for better decision making.